On the half shell: An introduction to oysters and their unique structures and function. (2nd January 2017) - Frederick, J. Adam; Haines, Sarah; Romano, Christina; Takacs, Jacqueline
Abstract: The eastern oyster, Crassostrea virginica, is an ecologically and economically important species in Chesapeake Bay. Oysters are ecologically unique in the Chesapeake Bay because they build a structure known as a bar or reef by attaching to one another over a 45 long period of time. They have been coined the "Ecological Engineers of the Bay". The main purpose of this activity is to investigate 5 uniquely designed organs of the eastern oyster (Crassostrea virginica). Emphasis is placed on two organs, the mantle and gills, and their ability to construct a pair of shells and to remove suspended materials from the water. Age-appropriate activities can be identified and performed in the elementary classroom that inspire inquiry and a better awareness of the relationship between structure and function and its importance for both the individual organism and the ecosystem in which it lives.